2022
DOI: 10.3233/jad-220432
|View full text |Cite
|
Sign up to set email alerts
|

Serum Uric Acid Levels in Neurodegenerative Disorders: A Cross-Sectional Study

Abstract: Background: Excessive oxidative stress may contribute to neurodegeneration by leading to protein aggregation and mitochondrial dysfunction. Uric acid (UA) is an important endogenous antioxidant that protects against oxidative stress, yet its exact role in neurodegeneration remains unclear. Objective: To explore the performance of serum UA in neurodegenerative disorders. Methods: A total of 839 controls and 840 patients, including Alzheimer’s disease (AD), Parkinson’s disease (PD), multiple system atrophy (MSA)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 58 publications
0
2
0
Order By: Relevance
“…It functions as a special free radical inhibitor and can chelate metal ions like iron and copper besides acting as a radical scavenger ( 52 ). Previous studies have shown a significant decrease in serum UA in PD ( 53 ),but these observational studies have many limitations in clearly stating the causal relationship between UA and PD. Recently, minority studies had used Mendelian randomization, although it is not clear whether there is a causal link between the two.…”
Section: Discussionmentioning
confidence: 99%
“…It functions as a special free radical inhibitor and can chelate metal ions like iron and copper besides acting as a radical scavenger ( 52 ). Previous studies have shown a significant decrease in serum UA in PD ( 53 ),but these observational studies have many limitations in clearly stating the causal relationship between UA and PD. Recently, minority studies had used Mendelian randomization, although it is not clear whether there is a causal link between the two.…”
Section: Discussionmentioning
confidence: 99%
“…While hyperuricemia is linked to oxidative stress and associated with various diseases, lower uric acid levels correlate with neurodegenerative disorders such as Alzheimer's and Parkinson's diseases. Uric acid also has neuroprotective effects in Parkinson's disease models (34,35). Despite evidence suggesting a potential association between elevated uric acid and dementia risk, particularly in Alzheimer's disease, the underlying mechanisms remain poorly understood.…”
Section: Introductionmentioning
confidence: 99%
“…It plays a crucial role in protecting against oxidative stress by interacting with reactive oxygen species (ROS) and converting non-enzymatically to allantoin. [28][29][30] Oxidative stress is one of the major mechanisms involved in the pathophysiology of central nervous system inflammation and neurodegenerative diseases. In some studies, higher levels of uric acid have been associated with a reduced risk of neurodegenerative diseases such as Parkinson's and Alzheimer's.…”
Section: Introductionmentioning
confidence: 99%